M. Lermontov’s and S. Esenin’s Patriotic Lyrics (Texas Journal of Philology, Culture and History, 2024)
In this article, the problem of studying the creative dialogue of poets, connected with the development of traditions and their interpretation, is one of the most urgent tasks of modern literary criticism.